Analisis Efisiensi Bank Umum Syariah Indonesia Periode Tahun 2011-2016 (Pendekatan Data Envelopment Analysis) - Dikdik Saleh Sadikin; Ramzi Ahmad Zuhdi; Fathoni Zoebaedi (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
This study aims to determine the level of efficiency in Sharia Commercial Bank in Indonesia period of 2011-2016. By using DEA Approach, input variables used are Third Party Fund, Labor Cost, Capital, while the output variable is Financing and Securities Owned. In the DEA approach, it suggests that bank size has an important role that determines its efficiency or relative inefficiency. The CCR model reflects (multiplication) technical efficiency and scale efficiency, while the BCC model reflects the technical efficiency only, so the relative scale efficiency is the ratio of the efficiency of the CCR model and the BCC model. From the analysis that has been done that 27% of sharia banking Indonesia has achieved efficiency, namely PT Bank Syariah Bukopin, PT BNI Syariah and PT Bank BCA Syariah and the remaining 63% have not been able to achievefull efficiency, the overall efficiency level is still around 92%, this is due to the inefficiency of several Banks such as PT Bank Syariah Bukopin. PT BNI Syariah, and PT Bank BCA Syariah, the three banks have average efficiency below the average value of the whole.